3-Pyridin-2-yl-1H-1,2,4-triazol-5-amine. - Dolzhenko, Anton; Tan, G.; Koh, L.; Dolzhenko, A.; Chui, W. (Blackwell Munksgaard, 2009)
In the title compound, C7H7N5, the non-H atoms are almost coplanar (r.m.s. deviation = 0.050 Å), with the N atom of pyridine ring oriented to the N-N(H) side of the 1,2,4-triazole ring. The mean planes of the pyridine and 1,2,4-triazole rings form a dihedral angle of 5.58 (7)degrees. The N atom of the amino group adopts a pyramidal configuration. The molecules are linked into a two-dimensional network parallel to (10) by N-H...N hydrogen bonds.